Relationship between hypercholesterolemia and sleep quality among older adults - Sari, Ayu Dwi Ratna; Sholihin, Sholihin; Toga, Erik (Palembang MediRose Publisher, 2023)
Background: Hypercholesterolemia refers to the buildup of fat in the blood, leading to the accumulation of fatty deposits on the walls of blood vessels, known as atherosclerosis. High cholesterol levels can adversely affect health, including the sleep quality of the older adults, leading to physical and psychological health issues. Objective: This study aims to examine the relationship between hypercholesterolemia and sleep quality among older adults. Methods: A cross-sectional design was utilized in this study, with a sample size of 60 respondents selected through purposive sampling. Data collection involved the use of a cholesterol level observation sheet and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. Data analysis was conducted using the Spearman Rank correlation. Results: The results revealed a significant relationship between hypercholesterolemia and sleep quality in the older adults (p < 0.0001; r = 0.802). This indicates a positive correlation between hypercholesterolemia and sleep quality among the older adults. Conclusions: The study concludes that as hypercholesterolemia levels become more normalized, sleep quality improves. Conversely, higher levels of hypercholesterolemia are associated with poorer sleep quality in the older adults.